Upaya Guru dalam Memberikan Layanan Konseling Siswa Kelas IV SD di Sekolah Alam Bengkulu Mahira - Zubaidah; Dea Fadilla Chairunisa; Hikmah Puspasari; Vera Wati; Ayu Safitri; Dea Puspitasari (Yayasan Darussalam Bengkulu, 2023)
This study raises the issue of how teachers' efforts are made in providing student counseling services. To answer the problem in this study, a qualitative descriptive research approach is used, namely explaining and presenting the results of research data regarding teachers' efforts in providing counseling services to fourth-grade elementary school students at Bengkulu Mahira Nature School. Data collection techniques used by researchers are observation, interviews and documentation to find out what efforts are made by teachers. The results of the study show that (1) The efforts of class teachers and assistant teachers in providing guidance and counseling services in responding to student problems are through good communication between teachers and students by providing direction if it has not been resolved, the teacher communicates with parents and if it has not been resolved, it will be brought to a higher level, namely the principal. (2) Obstacles experienced by teachers in providing guidance and counseling services when communicating with students who have different character differences. Teachers' efforts in providing guidance and counseling services can be carried out during learning, communicating with parents virtually or directly.